Strategic Management in Startups: Balancing Agility and Stability - Hemalatha P; Deepika Devi P (AG Volumes, 2024)
A start-up is an attractive business phenomenon that raises great expectations among founders and investors. The fulfillment of expectations is conditioned by the growth of business performance. In this article review the various literature’s study on Strategic Management in Startups. It concluded that strategic management in startups demands a balance between agility and stability for long-term success. Agility enables quick adaptation to market changes, fostering innovation and competitiveness. However, excessive agility can lead to erratic decisions and resource misallocation. Stability ensures operational consistency, financial sustainability, and resilience but may limit adaptability. Successful startups integrate both by fostering a learning culture, leveraging data-driven decisions, and implementing scalable processes. Continuous reassessment of market conditions and internal capabilities is crucial. By balancing agility and stability, startups can navigate uncertainties, drive innovation, and achieve sustainable growth in dynamic business environments.